Planning and international integration in Soviet Germany - STOLPER, W.F. (PSL Quarterly Review, 2014)
The German Democratic Republic has developed into a powerful member of the Soviet bloc, and yet little attention has so far been paid to it. The author argues that communist propaganda pictures developments in East Germany as a triumph of socialist planning over inherited backwardness, while free-market economists consider every failure as proof of imminent collapse. Instead, East Germany is a very interesting case of its own due to the peculiarity of its resource endowment as well as the recent history of bombing and war damage. JEL: O20, O52, P21